2019
DOI: 10.4187/respcare.06396
|View full text |Cite
|
Sign up to set email alerts
|

Study of Active Duty Military Personnel for Environmental Deployment Exposures: Pre- and Post-Deployment Spirometry (STAMPEDE II)

Abstract: BACKGROUND: There is significant concern about the respiratory health of deployed military service members given the reported airborne hazards in southwest Asia, which range from geologic dusts, burn pit emissions, chemical exposures, and increased rates of smoking. There has been no previous comparison of pre-and post-deployment lung function in these individuals. METHODS: Military personnel who deployed to southwest Asia in support of ongoing military operations were recruited from the Soldier Readiness Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
(24 reference statements)
1
25
0
2
Order By: Relevance
“…Indeed, trying to predict which military personnel are at risk for developing chronic respiratory issues has been evaluated in prior studies with mixed results. 2,7,13 The STAMPEDE II (Systemic Therapy in Advancing or Metastatic Prostate Cancer: Evaluation of Drug Efficacy) trial showed no significant difference in pre-and post-deployment spirometry and impulse oscillometry, including those who had baseline abnormal spirometry or asthma history. 7 The STAMPEDE III trial classified 32% of their subjects as having undiagnosed exertional dyspnoea with normal studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, trying to predict which military personnel are at risk for developing chronic respiratory issues has been evaluated in prior studies with mixed results. 2,7,13 The STAMPEDE II (Systemic Therapy in Advancing or Metastatic Prostate Cancer: Evaluation of Drug Efficacy) trial showed no significant difference in pre-and post-deployment spirometry and impulse oscillometry, including those who had baseline abnormal spirometry or asthma history. 7 The STAMPEDE III trial classified 32% of their subjects as having undiagnosed exertional dyspnoea with normal studies.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Confounding factors, such as predeployment exposures and undiagnosed pulmonary conditions, contribute to the difficulty in exploring this association. [6][7][8] The correlation of deployment to Southwest Asia with chronic lung disease continues to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…This brief correspondence is to address concerns regarding our manuscript, "Study of Active Duty Military Personnel for Environmental Deployment Exposures: Before and After Deployment Spirometry (STAMPEDE II)" by Morris et al published in the May 2019 issue of RESPIRATORY CARE. 1 Questions have been raised in several forums regarding the statistical analysis used in the original article. The original data involved the longitudinal collection of spirometry and impulse oscillometry values from soldiers prior to and after deployment to the theater of operations in southwest Asia.…”
Section: Individual Variation Of Spirometry Before and After Deploymementioning
confidence: 99%
“…The original data in the article were in fact analyzed using a paired t test approach, which takes advantage of the correlation between before and after deployment measures. 1 This was incorrectly reported as a Student t test in the article.…”
Section: Individual Variation Of Spirometry Before and After Deploymementioning
confidence: 99%
See 1 more Smart Citation